Factors Influencing Older Adults' End-of-Life Care Preferences. Issue 5 (12th October 2022) - Ke, Li-Shan; Hu, Wen-Yu; Dai, Yu-Tzu; Chen, Ching-Yu
Abstract : The objective of this study was to explore factors influencing Taiwanese older adults' end-of-life (EOL) care preferences. A cross-sectional questionnaire survey was conducted in 2 geriatric wards of a veterans' hospital. Fifty-five older adults aged 65 years or older were included. Structured questionnaires were used to collect data regarding demographic characteristics, EOL care preferences, stages of change for advance care planning behaviors, and reluctance to burden others. The study revealed that nearly 60% of the participants preferred to let their spouses, adult children, or health care professionals make the decisions. Furthermore, 83.6% of the participants lived with their family members and were moderately to severely disabled with a certain degree of dependence on their family members. Sex, independence, discussion of advance care planning with family members, and completion of advance directives were significantly correlated with EOL care preferences. The regression model showed that the participants' discussion of advance care planning with their family members influenced their EOL care preferences. The results demonstrate that family is an essential consideration for older adults choosing EOL care. Accordingly, because Chinese culture focuses on family harmony, improving communication between older adults and their family members is crucial for promoting advance care planning.